Pascal’s term esprit de géométrie - Khoma, Oleg (Sententiae, 2010)
There had been presented the differences in meaning, of the term esprit de géométrie as used by Pascal in fr. 511 and 512 (numerated by L. Lafyum) of his ” Thoughts”. It had been proved that in fr. 512 the term esprit de finesse is close in meaning to creative ingenium as used by Vico, and esprit de géométrie – to Descartes’s ingenium mathematicum. Besides that, Pascal’s esprit de géométrie, capable to simultaneously comprehend large amount of principles without mixing them, is obviously close to the Descartes’s studies on deduction and sagacitas, which appears in Regulae ad directionem ingenii (rule III).